Factors associated with adherence to the consumption of blood supplement tablets in female students at Senior High School 1 Godean Sleman Yogyakarta - Susanti, Dwi Susanti; Lutfiyani, Afi; Nursanti, Ida (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Adolescent girls have a ten times greater risk of anemia compared to young men. This is because adolescent girls experience menstruation every month and are in a period of growth that requires more iron intake. One form of anemia prevention in adolescents is the provision of blood supplement tablets. Based on the data, blood supplement tablets coverage is still low, indicating that adolescents' self-awareness to consume fe is still lacking. The purpose of this study was to determine what factors are associated with the compliance of female students in consuming blood supplement tablets. This study was conducted at senior high school 1 Godean with the research subjects were X and XI grade students totaling 81 students. Method: The sampling technique used was purposive sampling. The instruments used in this study were questionnaires about knowledge, family support, teacher support, peer support and health belief model (HBM) behavior questionnaire. The data obtained were then analyzed using univariate, bivariate and multivariate analysis. Results: The results of this study indicate that there are 3 factors associated with adherence to blood supplement tablets consumption in adolescents, namely peer support (p=0.02), perceived threat (p=0.02) and perceived self-efficacy (p=0.03). While the variables of knowledge (p=0.74), family support (p=0.51), teacher support (p=0.21), perceived susceptibility (p=0.24), perceived seriousness (p=0.41), perceived benefit (p=0.22), and perceived barrier (p=0.22) did not have a relationship with compliance in taking blood supplement tablets.